Photoactivation of Molecular Oxygen by an Iron(III) Porphyrin with a Magnesium Aluminum Layered Double Hydroxide for the Aerobic Epoxidation of Cyclohexene. Issue 8 (9th July 2014) - Teramura, Kentaro; Tsuneoka, Hideo; Ogura, Kentaro; Sugimoto, Takashi; Shishido, Tetsuya; Tanaka, Tsunehiro
Abstract The photocatalytic aerobic epoxidation of cyclohexene proceeded under visible‐light irradiation only if 5, 10, 15, 20tetrakis(pentafluorophenyl)porphyrin iron(III) chloride ([FeIII(TPFPP)Cl]) was combined with Mg‐Al layered double hydroxide (Mg‐Al LDH) as a solid base in chloroform. The OH groups in the Mg‐Al LDH exchanged with the axial Cl ligands in [FeIII(TPFPP)Cl] to afford [FeIII(TPFPP)OH], which functioned photocatalytically in the presence of Mg‐Al LDH but was inactive in its absence. The band in the action spectrum agreed well with the Soret band in the UV/Vis absorption spectrum of [FeIII(TPFPP)OH]. The spectral changes indicated the reduction of [FeIII(TPFPP)OH] to [FeII(TPFPP)] under visible‐light irradiation, which in turn activates O2 that could be used for the epoxidation of cyclohexene.